2002
DOI: 10.1046/j.1365-2095.2002.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental broodstock diets as partial fresh food substitutes in white shrimp Litopenaeus vannamei B.

Abstract: In the first experiment, conducted in a research facility, Litopenaeus vannamei broodstock were fed either a 100% fresh food control treatment (FRE, consisting of frozen squid, oyster, mussel and enriched Artemia biomass in a 2.3:1.4:1.3:1 dry matter ratio) or one of the two treatments in which 50% [dry matter (DM)] of the fresh food was substituted with experimental artificial diets: a dry diet based on freeze-dried Artemia biomass (ART) and a control dry diet (CON). In the second experiment, conducted in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Overall, the various combinations of squid, mussel, pellet, and Artemia tested performed well compared to squid–mussel or Artemia alone. Other studies have also demonstrated the inadequate nutrition provided by single or double item fresh diets and that a combination of natural and dry feeds as maturation outperforms fresh feeds hatchery practices (Nascimento et al 1991; Naessens et al 1997; Perez‐Velazquez et al 2002; Wouters et al 2002). Indeed when pellet was included in the diet of L. amboinensis in this study larval production increased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the various combinations of squid, mussel, pellet, and Artemia tested performed well compared to squid–mussel or Artemia alone. Other studies have also demonstrated the inadequate nutrition provided by single or double item fresh diets and that a combination of natural and dry feeds as maturation outperforms fresh feeds hatchery practices (Nascimento et al 1991; Naessens et al 1997; Perez‐Velazquez et al 2002; Wouters et al 2002). Indeed when pellet was included in the diet of L. amboinensis in this study larval production increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Such items include squid, mussel, polychaetes, and Artemia biomass, with artificial diets used only as a dietary supplement. This approach is because of generally poorer reproductive performance of artificial diets compared to the fresh ones (Nascimento et al 1991; Harrison 1997; Wouters et al 2000), although there has been successful partial or complete replacement of the classic fresh food regime with dry or moist diets in penaeids (Marsden et al 1997; Denece et al 1999; Wouters et al 2002).…”
mentioning
confidence: 99%
“…Valuable dietary compounds can be produced from recycling waste products. Marine polychaetes could be an important food for a variety of cultured species like marine prawns or flatfish (Pousao et al, 1995;Sudaryono et al, 1995;Costa et al, 2000;Wouters et al, 2002). Luis and Passos (1995) showed that the composition of the diet is a decisive factor in determining the fatty acid composition of N. diversicolor.…”
Section: Nereis Diversicolor As Potential Candidate For Integrated Aqmentioning
confidence: 97%
“…Coman & Crocos (2003) menyatakan bahwa daya tetas telur yang baik ditentukan oleh kondisi lingkungan pemeliharaan, keberhasilan pembuahan, mutu sperma, dan mutu telur. Faktor yang berpengaruh langsung pada performa reproduksi udang windu termasuk mutu spermatofor adalah nutrisi (Wouters et al, 2002;Coman et al, 2007;Hoa, 2009) dan lingkungan (Perez-Velazquez et al, 2001;Jiang et al, 2009;Mylonas et al, 2010).…”
Section: Performa Reproduksi Induk Betina Pasca Ib Dengan Jumlah Sperunclassified